Performances of Palm Oil Fuel Ash Cement Based Aerated Concrete in Acidic and Sulphate Environments - Mohd Warid, Hussin; Khairunisa, Muthusamy; Fadhadli, Zakaria (Istanbul Technical University, Turkey, 2008)
Malaysia as the world’s largest exporter of palm oil has been facing problem in disposing palm oil fuel ash, a by-product of palm oil mill since many years ago. The discovery made by researchers of Universiti Teknologi Malaysia last century in revealing the potential of this waste as a partial cement replacement in normal concrete has stem more efforts towards studying the possibility of using it in lightweight concrete production. Currently, investigation conducted proved that this material also can be integrated as a partial cement replacement material producing lightweight concrete known as Palm oil fuel ash cement based aerated concrete which possess adequate strength with lower density than OPC aerated concrete. This paper illustrates the durability aspect of this new agro blended cement based aerated concrete in terms of resistance towards aggressive chemicals such as acid and sulphate. Aerated concrete cube consisting 20% palm oil fuel ash and control specimen with 100% OPC were cast and then subjected to water curing for 28 days before immersed in the hydrochloric solution prepared using 0.3% hydrochloric acid having 99% concentration. The pH of the solution was controlled to about 2 throughout the immersion period of 1800 hours. The durability performance of the cubes involved the measurement of weight loss at a different period of immersion in the solution. In order to study the performance of this material in sulphate environment, a set of control specimen and another one consisting the same proportion of POFA were prepared before water cured for 28 days. Sulphate resistance of the binders was evaluated by measuring the expansion of mortar bars after immersion in 10% sodium sulphate solution for the period of 6 months. Finding will be discussing the performance of POFA cement based aerated concrete in both acidic and sulphate environments.